Peranan Kepolisian dalam Menangani Aksi Premanisme di Wilayah Hukum Polda Bali - I Komang Arya Kusumantara; I Nyoman Gede Sugiartha; Luh Putu Sudini (Fakultas Hukum, Universitas Warmadewa, 2022)
With the increasing number of residents also the number of evictions participated increased. This is also driven by the increasing population experiencing poverty, therefore encouraging people to commit crimes such as the many acts of thuggery. The focus of the research is to discuss the role of the police in dealing with thuggery acts in the Bali Police area and analyze the factors that cause thuggery acts in the Bali Police area. The method used in this research is the empirical legal method using a sociological approach. The research was carried out by taking data in the field as the main source of material, and books and journals as a secondary source. Data collection techniques using Observation Techniques in obtaining the data. Then, the results of the research explain that the role of the police in dealing with acts of thuggery in the Bali Regional Police is carried out using two efforts, namely preventive efforts including surveillance, patrolling, coaching and counseling. Repressive efforts include investigations, conducting raids in a structured manner. The factors that cause thuggery in the area protected by the Bali Police are caused by two factors, namely internal factors including thinking maturity and psychological pressure as well as internal factors.